Non specific immune response of batik lobster (Panulirus longipes) at different salinity - Muhammad Haikal Abdurachman; Adi Suriadin; Zulfiani Zulfiani (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Salinity has gave significant impact to stress levels that trigger of adjustment hemocyst with surroundings.The research aims to identify the Ideal maintenance of salinity on batik lobster (Panulirus longipes). It was conducted during at ninety days for maintanance period from September 2019 to Januari 2020 in Mata Shrimp Seeds Center, Kendari City. The Animals studied were batik lobsters (P. longipes) caught by nature with the male lobsters weighed 235±60 g and females were 237±50 g and total lobster under testing of 36 lobsters. The research had several test paremeters used to determine the effect of salinity such Osmotic Pressure (TKO), Total Hemocyte Count (THC) and histology of female gills. The statistical test Univariate Analysis of Variance and Duncan Test if (P<0.05) just used TKO parameters. The study discovered that TKO value of 833-1318 mOsmo/L with salinity exerting a strong influences (P<0.05). THC parameters of males showed a low stress response with a range of 3x106 - 14x106 cells/mL, it contrasts with the females had a high stress response with a range of 3x106 - 25x106cells/mL. The Conclusion was the male lobsters gave a low stress response with the ideal salinity of the cultivation, especially at 31⁰/ₒₒ and 34⁰/ₒₒ ware based on good response of maintenance TKO values and low stress levels on THC values